Pierre Bourdieu: theorizing the digital. Issue 7 (3rd July 2017) - Ignatow, Gabe; Robinson, Laura
ABSTRACT: Pierre Bourdieu is known for his research in the areas of education and cultural stratification that led to a number of theoretical contributions informing the social sciences. Bourdieu's interrelated concepts of field, capital, and habitus have become central in many approaches to inequality and stratification across the social sciences. In addition, we argue that Bourdieu's ideas also feature in what is increasingly known as 'digital sociology.' To underscore this claim, we explore the ways in which Bourdieu's ideas continue to have a major impact on social science research both on and with digital and Internet-based technologies. To do so, we offer a review of both Bourdieusian theorizing of the digital vis-à-vis both research on the social impacts of digital communication technologies and the application of digital technologies to social science research methods. We contend that three interconnected features of Bourdieu's sociology have allowed his approach to flourish in the digital age: (1) his theories' inseparability from the practice of empirical research; (2) his ontological stance combining realism and social constructionism; and (3) his familiarity with concepts developed in other disciplines and participation in interdisciplinary collaborative projects. We not only reason that these three factors go some way in accounting for Bourdieu's influence in many sociological subfields, but we also suggest that they have been especially successful in positioning Bourdieusian sociology to take advantage of opportunities associated with digital communication technologies.